Interaction between ANXA1 and GATA-3 in Immunosuppression of CD4+ T Cells - Peng Huang; Yuxiang Zhou; Zan Liu; Pihong Zhang (Hindawi Limited, 2016)
Decreased Th1/Th2 ratio is one of the major characteristics of immunosuppression in sepsis. Both membrane adhesive protein Annexin-A1 (ANXA1) and transcription factor GATA-3 have been reported to play important roles in T cell differentiation. However, the relationship between ANXA1 and GATA-3 in Th1/Th2 shift is unknown. Our study investigated the interaction effects of ANXA1 and GATA-3 to influence T cell differentiation in CD4+ T cells. We found that GATA-3 and ANXA1 were coexpressed on Th0/Th1/Th2 cytoplasm and nuclear. Overexpressed ANXA1 significantly increased the expression of IFNγ and reduced IL-4 expression in T cells, while ANXA1-silenced T cells exhibited decreased production of IFNγ and increased production of IL-4. Knockdown of ANXA1 promoted higher expression level of GATA-3 and low level of T-box transcription factor (T-bet/Tbx21). Further study demonstrated that ANXA1 regulated GATA-3 expression through the formyl peptide receptor like-1 (FPRL-1) downstream signaling pathways ERK and PKB/Akt. These results suggested that ANXA1 modulates GATA-3/T-bet expression induced Th0/Th1 differentiation. Moreover, we found that GATA-3 inhibited ANXA1 expression by binding to its promoter for the first time. It is proposed that the interactions between ANXA1 and GATA-3 may provide clues to understand the immunosuppression and have potential as new therapeutic targets in immunotherapy after sepsis.